The Relationship Between Workload and Burnout Among The Medical Staff In Hospital (Sains Humanika, 2021)
Prolonged occupational stress can lead to the syndrome of job burnout. Workload was one of the factors that can cause the burnout. The main objective of this study was to determine the levels of job burnout and their relationships with workload among the medical staff. The key roles of medical staff in a hospital can be broadly separated into four areas which were the doctors, nurses, allied health professionals and support staff. Eighty medical staff from hospital volunteered to participate in this research. Different data were gathered using the Maslach Burnout Inventory (MBI), NASA-Task Load Index and Demographic questionnaire. The significance of the study was to investigate the relationship between the job burnout and workload among the medical staff in hospitals. The overall level of workload and job burnout was moderate. The results indicated that workload and job burnout among medical staff in hospitals was at moderate level. There was a significant relationship between workload and job burnout in this research.
Keywords: Workload, Nasa-TLX, Job Burnout, Maslach Burnout Inventory (MBI), Medical Staff